Police Response to Narcotics Abuse Crimes in Sidoarjo: Tanggapan Kepolisian terhadap Kejahatan Penyalahgunaan Narkotika di Sidoarjo - Marsha Ivo Miranda; Emy Rosnawati (Academia Open, 2025)
General Background Narcotics abuse constitutes a serious criminal and public health problem in Indonesia, threatening social stability, security, and community welfare. Specific Background In Sidoarjo, East Java, reported cases of narcotics misuse have risen in recent years, particularly among adolescents and individuals of productive age, prompting intensified law enforcement and preventive measures by the local police narcotics unit. Knowledge Gap Despite the growing concern, limited documentation exists regarding operational practices, legal procedures, and challenges faced by regional police institutions in addressing narcotics crimes at the local level. Aims This study aims to describe the role, legal framework, and operational actions of the Sidoarjo City Police Narcotics Unit in handling narcotics abuse crimes based on an interview with a senior operational officer. Results The findings indicate that the police conduct both repressive enforcement against dealers and preventive activities, while drug users may undergo an assessment process leading to rehabilitation rather than imprisonment in accordance with national narcotics law. However, the unit encounters complex challenges, including sophisticated trafficking methods, resource limitations, and the involvement of diverse social groups. Novelty This work provides primary qualitative insight derived from practitioner testimony, offering a grounded depiction of institutional practices and challenges in a specific regional context. Implications Strengthening public education, increasing operational resources, advancing investigative capabilities, and fostering cross-sector collaboration are necessary to address narcotics abuse comprehensively at the community level. Highlights: Drug users may receive treatment placement following an integrated assessment rather than custodial sentencing. Trafficking networks employ increasingly sophisticated methods that complicate investigations. Multi-stakeholder cooperation and community participation are considered essential for suppression efforts. Keywords: Narcotics Abuse; Law Enforcement; Police Role; Rehabilitation Policy; Indonesia